Transformation and Adaptation of Traditional Culture in Contemporary Tourism: A Case Study of Kyoto Minshuku - Hu, Longxi (Transactions on Social Science, Education and Humanities Research, 2024)
Culture is a solid foundation for the development of tourism in Kyoto. Minshuku, as a product that meets the needs of culture tourism well, has been developing better and faster along with Kyoto’s tourism industry year by year. With the global modernization of cities, the preservation and balance of traditional culture has turned out to be an outstanding topic, and the role of Kyoto Minshuku in cultural heritage is an example worth studying under this broad topic. This paper specifically explores how minshuku, as a cultural carrier, can help traditional culture and old architecture find their place and play an important role in contemporary tourism. The key driving factors include the internal sale and remodeling needs of the old house, as well as the external tourism development, market demand, and policy support, among others. Meanwhile, this phenomenon has both positive and negative impacts on Kyoto’s society. As a case of effective transformation and adaptation of traditional culture, Kyoto’s minshuku has numerous references and examples for research in similar fields and many other urban planning, such as the combination of traditional culture and tourism, and the preservation and development of traditional culture.